DIGITAL-BASED FOLKTALE TEACHING MATERIALS THROUGH YOUTUBE MEDIA TO IMPROVE READING COMPREHENSION SKILLS OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Yogi Prayudi; Mira Nuryanti; Riskha Arfiyanti (Adisam Publisher, 2025)
This study aims to describe the strategy of integrating the Saung Galah Kingdom folktale as Indonesian language teaching material through YouTube and analyze its impact on improving literacy and character development in elementary school students. The method used is descriptive qualitative with a literature study and media development approach. The results show that educational videos based on folktales can increase students' reading interest, listening skills, and writing abilities. Local values such as leadership, honesty, and cooperation also contribute to shaping students' character from an early age. The local culture-based approach and digital media have proven relevant to contextual learning in the Independent Curriculum.